The analysis and utilization of cycling training data - Jobson, S. A.; Passfield, L.; Atkinson, G.; Barton, G.; Scarf , P. (Sports Medicine, 2009)
Most mathematical models of athletic training require the quantification of training intensity and quantity or `dose`. We aim to summarize both the methods available for such quantification, particularly in relation to cycle sport, and the mathematical techniques that may be used to model the relationship between training and performance.